Experimental investigation of heat transfer through Nitrogen and Argon gas in a closed space reactor vault model. Issue 8 (2nd July 2020) - Anish, M.; Jayaprakash, V.; Chandrasekar, P.
ABSTRACT: The main aim of this study is to analyse and understand the heat transfer in closed spaces between the main vessel and the safety vessel in a nuclear reactor by using Nitrogen and Argon gas as an insulator. For nuclear reactor cooling, researchers started moving from the hard water method to various other methods of dissipating the heat. In this study, we used a closed cube filled with nitrogen as a prototype model. Within the closed cube, a very thin pipe is used to carry the nitrogen gas and Argon gas, whose effectiveness will be measured in the study. This study is conducted into three parts, with the main thing being creating a proto-model to conduct the experiment.